Comparison of Employment Impacts of Renewable and Fossil Energy Based Electricity Sectors: The Case of Turkey - Yahya Algül; Vedat Kaya (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Considering rapidly rising air pollution and unemployment problem in Turkey, renewable energy may be the most appropriate solution for both of the problems. While positive effect of renewable energy on the environement is widely acknowledged, there isn’t sufficient research about its effect on employment statistics. For this reason, in this study, the net employment benefit of the renewable-based electricity sector, against the fossil-based electricity sector, is investigated through Input-Output methodology. The estimation is done for both manufacturing/installation and operation/maintenance phases of solar, wind, hydropower, bioenergy, geothermal, coal, petrol, and natural gas-based electricity sectors, including all of the direct, indirect, and induced effects. According to the estimation results of both approaches and both of the phases, renewable-based electricity sectors are more effective than fossil-based electricity sectors in terms of employment generation. Therefore, besides its claimed benefits in terms of environment, the renewable energy sector may be a major instrument in the sustainable development efforts in Turkey, considering its employment benefits too.